The process of education - Bruner, Jerome S. (Cambridge : Harvard University Press, 1977)
Jerome Bruner shows that the basic concepts of science and the humanities can be grasped intuitively at a very early age. Bruner's foundational case for the spiral curriculum has influenced a generation of educators and will continue to be a source of insight into the goals and methods of the educational process.
Includes index.
Keywords: Education -- Aims and objectives; Teaching